Economic Efficiency of Exporting Queen Bees and Bee Packages from America to Canada and England - Olshanskyi, Oleksandr (Здобутки економіки: перспективи та інновації, 2025)
The relevance of the study is due to the high demand for high-quality queen bees and bee packages in countries with insufficient domestic production, in particular in Canada and England. The limited queen rearing season in northern climates and the need for a stable supply of high-quality breeding material create significant opportunities for expanding exports from the Americas. At the same time, the efficiency of such exports depends on numerous economic and logistical factors, which requires a detailed analysis. The purpose of the article is to comprehensively assess the economic efficiency of exporting queen bees and bee packages from America to Canada and England, taking into account the specifics of market conditions, costs, logistics and profitability. The research methods are based on the use of economic, statistical and comparative analysis, a systematic approach and expert assessments.The results of the study indicate a significant potential for American exports of queen bees and packages due to high quality products and favorable growing conditions. The main factors affecting the economic efficiency of exports are identified: production costs, transportation costs, certification and customs clearance. It is proved that the demand for imported queen bees in Canada and England remains consistently high due to limited domestic production capacity. The conclusions of the studyemphasize the importance of optimizing production and logistics processes, improving certification and customs clearance procedures, as well as actively introducing modern breeding methods to ensure high competitiveness of American exporters in the international market. Practical recommendations for increasing the profitability of export operations and expanding cooperation with Canadian and British partners are proposed. The results obtained are important for the formation of an effective export strategy and the development of international cooperation in the field of beekeeping.